The Correlation Betweent Students Motivationand Their Achievement Score in Learning English at 11th grade of Ashhabul Yamin Islamic Boarding School - Angeliani, Febi; Sakti, Genta; Eliza, Eliza; Syahrul, Syahrul (Pusdikra-Publishing.com, 2024)
Most of the problems that arise indicate lack of motivation of grade 1 students of the Ashhabul Yamin Islamic boarding school.For example, most students are not interested in learning English, less motivational words from the teacher.Many students do not complete their homework at home and also many students think English is a difficult subject because they don't have anyone to support them directly including their classmates. This study aims to determine whether there is a relationship between student motivation and student academic achievement in learning English. This research is a correlational research. Total population is 44 students, the sample is 26 students. Researchers used purposive sampling on determine the sample in this study. To collect data, researchers use questionnaire and documentation. To analyze the data collected, researchers useSpearman's Rating Correlation Coefficient (and to test the hypothesis,the researcher uses the t-test formula and consults the results into the t-table with = 0.05. The finding of the research revealed that the coefficient of correlation ( was -0.115. It means, there is no correlation between extrinsic motivation and students’ academic achievement in studying English. In the other words, based on hypothesis testing, the t- score was -0.114 whereas t-table on = 0,05 was 0.404. It means, the tscore was smaller than the t-table. Hence, Ha rejected and Ho accepted, which stated that there is no significant correlation between students motivation and students’ achievement in studying English.